Low-intensity pulsed ultrasound promotes the osteogenesis of mechanical force-treated periodontal ligament cells via Piezo1 - Zheng, Fu; Wu, Tong; Wang, Feifei; Li, Huazhi; Tang, Hongyi; Cui, Xinyu; Li, Cuiying; Wang, Yixiang; Jiang, Jiuhui (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Low-intensity pulsed ultrasound (LIPUS) can accelerate tooth movement and preserve tooth and bone integrity during orthodontic treatment. However, the mechanisms by which LIPUS affects tissue remodeling during orthodontic tooth movement (OTM) remain unclear. Periodontal ligament cells (PDLCs) are pivotal in maintaining periodontal tissue equilibrium when subjected to mechanical stimuli. One notable mechano-sensitive ion channel, Piezo1, can modulate cellular function in response to mechanical cues. This study aimed to elucidate the involvement of Piezo1 in the osteogenic response of force-treated PDLCs when stimulated by LIPUS.Method: After establishing rat OTM models, LIPUS was used to stimulate rats locally. OTM distance and alveolar bone density were assessed using micro-computed tomography, and histological analyses included hematoxylin and eosin staining, tartrate-resistant acid phosphatase staining and immunohistochemical staining. GsMTx4 and Yoda1 were respectively utilized for Piezo1 functional inhibition and activation experiments in rats. We isolated human PDLCs (hPDLCs) in vitro and evaluated the effects of LIPUS on the osteogenic differentiation of force-treated hPDLCs using realtime quantitative PCR, Western blot, alkaline phosphatase and alizarin red staining. Small interfering RNA and Yoda1 were employed to validate the role of Piezo1 in this process.Results: LIPUS promoted osteoclast differentiation and accelerated OTM in rats. Furthermore, LIPUS alleviated alveolar bone resorption under pressure and enhanced osteogenesis of force-treated PDLCs both in vivo and in vitro by downregulating Piezo1 expression. Subsequent administration of GsMTx4 in rats and siPIEZO1 transfection in hPDLCs attenuated the inhibitory effect on osteogenic differentiation under pressure, whereas LIPUS efficacy was partially mitigated. Yoda1 treatment inhibited osteogenic differentiation of hPDLCs, resulting in reduced expression of Collagen Ⅰα1 and osteocalcin in the periodontal ligament. However, LIPUS administration was able to counteract these effects.This research unveils that LIPUS promotes the osteogenesis of force-treated PDLCs via downregulating Piezo1.